PEMBUATAN PEMBUATAN PRODUK LAUNDRY SEBAGAI USAHA RUMAH TANGGA RAMAH LINGKUNGAN DI DESA DUMAN KECAMATAN LINGSAR KABUPATEN LOMBOK BARAT - MAYA - EKANINGTIAS (Alamtana: Jurnal Pengabdian Masyarakat UNW Mataram, 2020)
Abstract: Household activity such as washing clothes (laundry) is a routine activity. And as we know, a lot of laundries products circulate commercially in the community. But the price of the products is expensive, and we spent a lot of money to buy them. In the village of Duman there are many laundries businesses, and laundries products are necessary. Based on the result, the team of community service which are lecturers from biology education department in FKIP UNW Mataram, made a training camp to produce laundry products for villagers in order to make their own home business, especially for laundry products. The activities were carried out for 12 hours in the village of Duman, continued with assistance for 2 days. Laundry products that were made include laundry perfume, softener, and softstrika.